Environmental sustainability in Turkey: an environmental Kuznets curve estimation for ecological footprint. Issue 3 (3rd April 2021) - Bulut, Umit
ABSTRACT: The goal of this paper is to detect the determinants of ecological footprint (EF) in Turkey within the scope of the environmental Kuznets curve (EKC) hypothesis over the period 1970–2016. For this purpose, the paper sets up an empirical model including GDP, the square of GDP, foreign direct investments, renewable energy consumption, and industrialization. Hence, the paper also searches for the validity of the pollution haven hypothesis (PHH) for Turkey. The findings of the paper indicate that the EKC hypothesis prevails, whereas the PHH does not dominate in Turkey. The findings also imply EF is negatively related to renewable energy consumption while industrialization does not affect EF. Theoretical and practical implications are discussed.